Analisis Pendapatan Asli Daerah Melalui Kontribusi Pajak dan Retribusi Daerah dalam Meninjau Peraturan Daerah Pamekasan - Kamaroellah, R. Agoes (Unversitas Islam Madura, 2024)
The contribution of regional taxes and levies plays an essential role in the local government's development. The greater the original local government revenue, the greater the financing that the local government must issue to develop their region. This study aims to determine the size of the contribution of taxes collected by regions and local levies in increasing Original Local Government Revenue in the Pamekasan Regency from 2011 to 2017. This type of research was a quantitative descriptive study. Based on regional financial statistics, the results of local taxes and levies from 2011 to 2017 experienced fluctuating movements that impacted Original Local Government Revenue. It means that local taxes and levies contribute to increasing Original Local Government Revenue. On average, each year, the contribution of local taxes reached 13%, while for local levies, it reached 12% for Original Local Government Revenue. With this achievement, the Pamekasan district government can review regional provisions in the form of Local Government Regulation relating to the number of local tax rates and levies.